WAYS OF USING MARKETING STRATEGIES IN THE DEVELOPMENT OF LOGISTICS SERVICES OF FREE ECONOMIC ZONES (Marketing Journal, 2026)
This scientific article examines the theoretical and practical aspects of using marketing strategies in the development of logistics services in free economic zones. In particular, the study highlights the main factors influencing the efficiency of logisti cs services in free economic zones, including issues related to the coordinated management of material, information, and financial flows. In addition, the article reveals the content of territorial marketing strategy, service differentiation strategy, № 1 -SON YANVA R, 202 6-YIL 403 digital marketing strategy, and co -marketing strategy applied in the development of logistics services in free economic zones, as well as the ways of their implementation.
Keywords: free economic zones; development of logistics services; territorial marketing strategy; service differentiation strategy; digital marketing strategy; co - marketing; transport and logistics potential; investment attractiveness